Wreck/Conciliation? The Politics of Truth Commissions in Thailand. (December 2014) - McCargo, Duncan; Thabchumpon, Naruemon
Abstract : More than ninety people died in political violence linked to the March–May 2010 "redshirt" protests in Bangkok. The work of the government-appointed Truth for Reconciliation Commission of Thailand (TRCT) illustrates the potential shortcomings of seeing quasi-judicial commissions as a catch-all solution for societies struggling to deal with the truth about their recent pasts. The 2012 TRCT report was widely criticized for blaming too much of the violence on the actions of rogue elements of the demonstrators and failing to focus tightly on the obvious legal transgressions of the security forces. By failing strongly to criticize the role of the military in most of the fatal shootings, the TRCT arguably helped pave the way for the 2014 coup. Truth commissions that are unable to produce convincing explanations of the facts they examine may actually prove counterproductive. Following Quinn and Wilson, we argue in this article that weak truth commissions are prone to politicization and are likely to produce disappointing outcomes, which may even be counterproductive.